Evaluation of the oral corticosteroid-sparing effect of tezepelumab in adults with oral corticosteroid-dependent asthma (SOURCE): a randomised, placebo-controlled, phase 3 study. Issue 7 (July 2022) - Wechsler, Michael E; Menzies-Gow, Andrew; Brightling, Christopher E; Kuna, Piotr; Korn, Stephanie; Welte, Tobias; Griffiths, Janet M; Sałapa, Kinga; Hellqvist, Åsa; Almqvist, Gun; Lal, Harbans; Kaur, Primal; et al.
Summary: Background: Tezepelumab is a human monoclonal antibody that blocks the activity of thymic stromal lymphopoietin. SOURCE evaluated the oral corticosteroid-sparing effect of tezepelumab in adults with oral corticosteroid-dependent asthma. Methods: We conducted this phase 3, multicentre, randomised, double-blind, placebo-controlled study across 60 sites in seven countries. Participants aged 18–80 years with physician-diagnosed asthma, who had been receiving medium-dose or high-dose inhaled corticosteroids and had at least one asthma exacerbation in the 12 months before screening were eligible. Patients who were receiving medium-dose inhaled corticosteroids must have had their dose increased to a high dose for at least 3 months before screening. After an oral corticosteroid optimisation phase of up to 8 weeks, participants were randomly assigned according to a computer-generated fixed block randomisation sequence to receive tezepelumab 210 mg or placebo subcutaneously every 4 weeks during a 48 week treatment period (4 week induction phase, 36 week oral corticosteroid reduction phase, and 8 week maintenance phase). Randomisation was stratified by region. Participants, investigators, and site staff were masked to treatment assignment. The primary endpoint was the categorised percentage reduction from baseline in daily oral corticosteroid dose at week 48 without the loss of asthma control. Efficacy and safety endpoints were assessed in all participants who received at least one dose of study drug. This study is registered with ClinicalTrials.gov, NCT03406078 . Findings: Between March 5, 2018, and Sept 27, 2019, 150 participants were randomly assigned to receive tezepelumab 210 mg (n=74) or placebo (n=76). The cumulative odds of achieving a category of greater percentage reduction in an oral corticosteroid dose for daily maintenance at week 48 were similar with tezepelumab or placebo in the overall population (odds ratio [OR] 1·28 [95% CI 0·69–2·35], p=0·43; the primary endpoint was not met). The cumulative odds were higher with tezepelumab than with placebo in participants with baseline blood eosinophil counts of at least 150 cells per μL (2·58 [1·16–5·75]), but not in participants with counts below 150 cells per μL (0·40 [0·14–1·13]). Tezepelumab was well tolerated, with no safety concerns identified. 53 (72%) of 74 tezepelumab-assigned participants and 65 (86%) of 76 placebo-assigned participants reported an adverse event. Serious adverse events were reported in 12 (16%) participants in the tezepelumab group and 16 (21%) participants in the placebo group. Interpretation: We did not observe a significant improvement in oral corticosteroid dose reduction with tezepelumab versus placebo in the overall population of this oral corticosteroid-sparing study, although an improvement was observed in participants with baseline blood eosinophil counts of at least 150 cells per μL. Funding: AstraZeneca and Amgen.